Bioapplications of hyperbranched polymers - Wang, Dali; Zhao, Tianyu; Zhu, Xinyuan; Yan, Deyue; Wang, Wenxin (Chemical Society reviews, 2015)
Hyperbranched polymers (HBPs), an important subclass of dendritic macromolecules, are highly branched, three-dimensional globular nanopolymeric architectures. Attractive features like highly branched topological structures, adequate spatial cavities, numerous terminal functional groups and convenient synthetic procedures distinguish them from the available polymers (the linear, branched, and crosslinking polymers). Due to their unique physical/chemical properties, applications of HBPs have been explored in a large variety of fields. In particular, HBPs exhibit unique advantages in the biological and biomedical systems and devices. Firstly, the way to prepare HBPs usually only involves simple one-pot reactions and avoids the complicated synthesis and purification procedures, which makes the manufacturing process more convenient, thus reducing production costs. Secondly, the large number of end-groups of HBPs provides a platform for conjugation of the functional moieties and can also be employed to tailor-make the properties of HBPs, enhancing their versatility in biological applications. Thirdly, HBPs possess excellent biocompatibility and biodegradability, controlled responsive nature, and ability to incorporate a multiple array of guest molecules through covalent or noncovalent approaches. All of these features of HBPs are of great significance for designing and producing biomaterials. To date, significant progress has been made for the HBPs in solving some of the fundamental and technical questions toward their bioapplications. The present review highlights the contribution of HBPs to biological and biomedical fields with intent to aid the researchers in exploring HBPs for bioapplications. The recent research progress in biological and biomedical applications of hyperbranched polymers has been summarized in this review.